A Política educacional para o Maranhão: uma (re)visão nas diretrizes e estratégias para a reestruturação do ensino médio - COSTA, Rosangela Mendes (Universidade Federal do Pará, 2013)
This thesis aims to analyze the mediations understood as mechanism and actions, proposed by SEDUC/MA, taken from the LDB - Law Nº. 9.394/96 -, from DCNEM and PCNEM, and from the Guidelines and Strategies for Educational Policy of the State of Maranhão, which guided the high school restructuring. It explains the fundamentals and principles of the high school reform, considering the socioeconomic and political context that influenced the development of educational policies and guidelines since the 1990s, examining the strategies and guidelines that defined the educational policy in the state and verifying the literature review, documentary analysis and analysis of mechanisms and actions that were adopted by the Secretariat to implement their high school‟s policy. In the course of the study was evidenced the influence of capital globalization and implementation of mediations adopted by SEDUC/MA to concretize that policy. It is a quantitative documentary research, based on the dialectic history and dialectic materialism, and based on procedures the productive restructuring, as well as the educational policies at the national level, on the educational policy of Maranhão. Such influences were explicited in legislations that indicated the principles and guidelines that guided the administrative and pedagogical organization of the education systems and the schools themselves, as emphasis on interdisciplinary, contextualization and skills training. The study also showed that the guidelines and strategies that guided the educational policy of the State of Maranhão and the implemented mechanisms for its realization, which were the Curriculum References of the High School, the Guidelines for the Assessment of Learning and the Training Plan, presented weaknesses in their conceptions and in their implementation process, reflecting in the school performance indicators. It also revealed that these strategies did not produce a qualified high school in the state.